2018
DOI: 10.1080/1745039x.2018.1458459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellobiose supplementation and dietary soluble fibre content on in vitro caecal fermentation of carbohydrate-rich substrates in rabbits

Abstract: The in vitro caecal fermentation of five substrates low in starch and protein content [d-(+)-glucose (GLU), d-cellobiose (CEL), sugar beet pectin (PEC), sugar beet pulp (SBP) and wheat straw (WS)] was investigated using soft faeces from rabbits receiving different levels of cellobiose and soluble fibre as inoculum. A total of 24 rabbits were supplemented 3 levels of cellobiose in the drinking water (0.0, 7.5, 15.0 g/l) and fed two experimental diets containing either low soluble fibre (LSF) or high soluble fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
4
4
1
Order By: Relevance
“…The increase of SF when NDF is low (LIF-HSF vs. LIF-LSF) improved both NDF and SF digestibility in agreement with previous studies [7,9,23]. It is explained by the faster digestion rate of SF, similar to that observed in vitro for SBP when compared with straw [36]. The increase of NDF when SF is high (HIF-HSF vs. LIF-HSF) improved also the NDF and SF digestibility as expected [37,38] but the NDF to a lesser extent.…”
Section: Discussionsupporting
confidence: 90%
“…The increase of SF when NDF is low (LIF-HSF vs. LIF-LSF) improved both NDF and SF digestibility in agreement with previous studies [7,9,23]. It is explained by the faster digestion rate of SF, similar to that observed in vitro for SBP when compared with straw [36]. The increase of NDF when SF is high (HIF-HSF vs. LIF-HSF) improved also the NDF and SF digestibility as expected [37,38] but the NDF to a lesser extent.…”
Section: Discussionsupporting
confidence: 90%
“…FSG was highly fermented by rabbits’ caecal microflora because of its high carbohydrate content, which is positively correlated with the maximum cumulative volume of gas production [ 51 ]. The fermentative behaviour of FSG was similar to that shown by other soluble fibre sources in rabbits [ 52 , 53 ], having a maximum gas production rate (3.1 to 3.7 mL/h) between that of sugar beet pulp (2.9 mL/h) and that of pectin (6.0 to 8.0 mL/h). The high level of microbial fermentation of FSG might imply high energy losses, which may require a nitrogen source supplementation.…”
Section: Discussionsupporting
confidence: 71%
“…LIF-LSF) improved both NDF and SF digestibility in agreement with previous studies (Trocino et al, 2013;Abad-Guamán, 2015;Delgado et al, 2019). It is explained by the faster digestion rate of SF, similar to that observed in vitro for SBP when compared with straw (Ocasio-Vega et al, 2018a). The increase of NDF when SF is high (HIF-HSF vs. LIF-HSF) impaired the NDF and SF digestibility that partially agreed with previous results (Caîsin et al, 2020;.…”
Section: Calculations Of Energy and Nitrogen Efficiencysupporting
confidence: 91%
“…It would suggest that the dietary insoluble fibre level should be limited after weaning. The digestive symptoms during the trial pointed to ERE, but the most affected groups (HIF) showed an increase of caecal pH instead of the caecal acidification we found during ERE outbreaks (Gómez-Conde et al, 2007;Ocasio-Vega et al, 2018a), although this was not observed in other farms (Martínez-Vallespín et al, 2011). The highest caecal pH found in HIF-LSF group might be associated to its high ileal protein flow and a potential higher ammonia concentration in the caecum that would agree with the higher urinary nitrogen losses reported in Exp.…”
Section: Calculations Of Energy and Nitrogen Efficiencysupporting
confidence: 81%
See 1 more Smart Citation